2022
DOI: 10.1111/ppc.13114
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between violence against women and gender attitudes in men, Bolu province Kıbrıscık example

Abstract: Purpose:The study has two purposes: "ascertaining the determinants and the frequency of violence against women in men" and "determining the relation between men's violence against women and gender attitudes."Design and Methods: The study is of cross-sectional type. Three questionnaires were used to collect the research data: sociodemographic information form, violence against women questionnaire, and the Gender Equality Scale. Findings:The first important finding of the study is that the rate of domestic viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Similar to this result, in another study, those living in the city were shown to have high attitudes towards violence against women (Polat et al 2021). Meanwhile, low socioeconomic status negatively affects individuals' attitudes towards violence against women (Özpınar and Acar 2022). Communities living in low socio-economic status are at risk in terms of perpetrating and accepting violence against women.…”
Section: Discussionsupporting
confidence: 69%
“…Similar to this result, in another study, those living in the city were shown to have high attitudes towards violence against women (Polat et al 2021). Meanwhile, low socioeconomic status negatively affects individuals' attitudes towards violence against women (Özpınar and Acar 2022). Communities living in low socio-economic status are at risk in terms of perpetrating and accepting violence against women.…”
Section: Discussionsupporting
confidence: 69%